Balancing clinical needs and probation requirements within CSEC specialty courts. (24th June 2022) - Gale‐Bentz, Elizabeth; Iturri, Florencia; Wheeler, Tracey; Nelke, Connie F.
Abstract: As juvenile justice systems across the country explore ways to best serve youth who have been commercially sexually exploited, challenges may arise between youths' clinically indicated needs and the probation‐driven requirements of CSEC specialty court involvement. This article explores some of the clinical‐probation dualities CSEC specialty courts may encounter, conceptualized as tensions related to issues of confidentiality, responses to behaviors that jeopardize youths' safety, and the timing of healing. Future directions for consideration to better meet the needs of youth involved in the justice system who have experienced sexual exploitation are also discussed.